Transparent and Black Film Mulching Improve Photosynthesis and Yield of Summer Maize in North China Plain - Shanshan Qin; Yanqun Zhang; Jiandong Wang; Chuanjuan Wang; Yan Mo; Shihong Gong (Agriculture, 2022)
In order to clarify the influences of drip irrigation under different mulch materials on crop yield, field experiments were carried out in the North China Plain for two seasons in 2020 and 2021. The changes in field microenvironment, photosynthetic capacity, leaf biological factors, and maize growth indexes were analyzed under drip irrigation with transparent film (W), black film (B), and straw mulching (S), with a nonmulching field as control (CK). The results showed that compared with CK, the yield of W and B increased by 7.2–9.9% and 7.1–12.4%, and the yield of S did not change significantly. The increase in yield was related to the improvement of the field microenvironment and photosynthetic capacity and higher LAI. Compared with CK, the soil water content 0–40 cm below the soil surface of W, B, and S increased by 13.6%, 9.1%, and 4.6%, respectively, and the 5 cm effective accumulated soil temperature of W and B increased by 7.9–10.2% and 4.1–4.7%, respectively. The maximum carboxylation rate (Vmax) of W, B, and S at the jointing stage was significantly increased by 3.5–17.3%, 12.7–17.6%, and 10.1–12.7% compared with CK. There was a significant linear correlation between Vmax and Nmass, and the correlation was affected by mulching treatments. At the jointing stage, compared with the CK, the LAI of W and B significantly increased by 8.6–66.5% and 7.2–56.0%, but there was no significant difference between S and CK. In conclusion, the increase in yield of W and B resulted from the combined effect of increasing LAI, Vmax, and soil water content and temperature.